Morpho-anatomical characterization and DNA barcode of Cosmos caudatus Kunth. - HERY PURNOBASUKI; GALUH AYU RAKHASHIWI; JUNAIRIAH JUNAIRIAH; DWI KUSUMA WAHYUNI; RAMADHANI EKA PUTRA; RIKA RAFFIUDIN; RC HIDAYAT SOESSILOHADI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Purnobasuki H, Rakhashiwi GA, Junairiah, Wahyuni DK, Putra RE, Raffiudin R, Soessilohadi RCH. 2022. Morpho-anatomical characterization and DNA barcode of Cosmos caudatus Kunth. Biodiversitas 23: 4097-4108. Secondary metabolites in plants have various benefits, therefore their distribution in plant body parts is important to study. The identification process of plants should be conducted using several characters, including morphological and molecular data. This study aimed to identify and confirm Cosmos caudatus Kunth using morpho-anatomy characters and DNA barcodes. The plants used were three samples taken from the Husada Graha Famili Park, Surabaya. The morpho-anatomical investigation was carried out descriptively, while the DNA barcoding study was processed by amplifying and sequencing the rbcL and matK genes. Morphological studies indicate that the roots and stems of C. caudatus are similar to the organs of dicots shrubs in general. The leaves have a pinnate type with two different colors on each side of the leaf. Compound flowers are cup-type with two types of flowers, namely disc flowers and ray flowers. Based on anatomical observation, all vegetative organs have the same tissue as dicotyledonous plants. The anatomical characteristic of C. caudatus lies in its trichomes due to its anthocyanin content and stomata which are anomocytic and anisocytic types. DNA barcoding results showed that the three sample plants had identical similarities with several Cosmos genera contained in the GenBank database with percentage identities values ??above 98%, query covers 96-100%, and e-values ??of 0.